Bioavailable vitamin D levels are reduced and correlate with bone mineral density and markers of mineral metabolism in adults with nephrotic syndrome. Issue 6 (June 2016) - Aggarwal, Abhinav; Yadav, Ashok K; Ramachandran, Raja; Kumar, Vinod; Kumar, Vivek; Sachdeva, Naresh; Khandelwal, Niranjan; Jha, Vivekanand
Abstract: Aim: Blood levels of 25‐hydroxyvitamin D [25(OH) D] are reduced in patients with nephrotic syndrome (NS). The lowering is thought to be due to urinary loss of vitamin D binding protein (DBP). A link between vitamin D deficiency and bone disease or markers of mineral metabolism has not yet been shown in NS. We hypothesized that alterations in bioavailable vitamin D levels might be linked to these abnormalities in NS. Methods: We measured circulating levels of 25(OH)D, 1, 25‐dihydroxyvitamin D [1, 25(OH)2 D], DBP, serum albumin and intact parathyroid hormone (iPTH) in 106 adults with sporadic idiopathic NS and 40 healthy controls. Bioavailable vitamin D was calculated from previously validated formulae. Bone mineral density (BMD) was measured at left hip (neck of femur) by DEXA. Results: Compared to healthy controls, total and bioavailable 25(OH)D levels were significantly reduced in patients with NS as compared to healthy controls. Among the nephrotic patients, BMD was positively correlated with bioavailable 25(OH)D (r = 0.358; P = 0.0002) but not with total 25(OH)D (r = 0.174; P = 0.079). Total 1, 25(OH)2 D and bioavailable 1, 25(OH)2 D did not correlate with BMD (r = 0.131; P = 0.206 and r = 0.107, P = 0.295). Bioavailable 25(OH)D levels showed a strong inverse correlation with iPTH on univariate (r = −0.457; P < 0.0001) and multivariate (β=−0.453, P < 0.0001) analyses. Conclusions: We conclude that bioavailable 25(OH)D is a better measure of vitamin D status with respect of BMD and mineral metabolism in patients of nephrotic syndrome. Summary at a Glance: The authors examine the impacts of free, albumin bound and VDBP bound total circulating 25(OH)D and 1, 25 di(OH)D concentrations in primary nephrotic syndrome patients and the relationship with a single site BMD. The paper concludes that bio‐available 25(OH)D is a better measure of vitamin D status with respect to BMD and mineral metabolism in patients with the nephrotic syndrome.